If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 41 + -1x = 3(5x + 3) Reorder the terms: 41 + -1x = 3(3 + 5x) 41 + -1x = (3 * 3 + 5x * 3) 41 + -1x = (9 + 15x) Solving 41 + -1x = 9 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 41 + -1x + -15x = 9 + 15x + -15x Combine like terms: -1x + -15x = -16x 41 + -16x = 9 + 15x + -15x Combine like terms: 15x + -15x = 0 41 + -16x = 9 + 0 41 + -16x = 9 Add '-41' to each side of the equation. 41 + -41 + -16x = 9 + -41 Combine like terms: 41 + -41 = 0 0 + -16x = 9 + -41 -16x = 9 + -41 Combine like terms: 9 + -41 = -32 -16x = -32 Divide each side by '-16'. x = 2 Simplifying x = 2
| F(X)=3X-4+X(9X-7) | | 3h^2-60=24h | | 9y+5x=10 | | y=11x^2+5x+13 | | 3h+9=4h-3 | | c+3=15-3c | | (x-80)/X=0.2 | | 4(2x-4)=8x+56 | | 4(2x-4)=8x+36 | | 4(2x-4)=8x+20 | | 4(2x-4)=8x+19 | | 4(2x-4)=8x+18 | | 4(2x-4)=8x+17 | | 4(2x-4)=8x+15 | | 4(2x-4)=8x+14 | | 4(2x-4)=8x+12 | | 3cosx+5sinx-5=0 | | 4(2x-4)=8x+0 | | 4(2x-4)=8x+9 | | 4(2x-4)=8x+7 | | 4(2x-4)=8x+6 | | 4(2x-4)=8x+5 | | 4(2x-4)=8x+80 | | 4(2x-4)=8x+24 | | 4(2x-4)=8x+8 | | 4(2x-4)=8x+3 | | 4(2x-4)=8x+2 | | 4(2x-4)=8x+1 | | 3-2(x+4)=-17 | | 4(2x-4)=8x+4 | | 4(2x-4)=8x+32 | | 4(2x-4)=8x+ |